2011
DOI: 10.1016/s0016-5085(11)63960-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Morbidity Associated With Muscle Cramps in Patients With Cirrhosis

Abstract: PURPOSE-Patients with cirrhosis often experience muscle cramps with varying severity. We investigated the factors associated with the prevalence and morbidity associated with muscle cramps.METHODS-A total of 150 adult patients with cirrhosis were enrolled consecutively. Cramp questionnaire with visual analogue scale for pain, Chronic Liver Disease Questionnaire (CLDQ), and blood for measurement of 25-(OH) vitamin D levels were obtained after informed consent.RESULTS-A total of 101 patients (67%) reported muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…L-carnitine supplementation resulted in a decrease in the frequency of muscle cramps and in Wong-Baker FACES ® Pain Rating Scale score, and associated with an increase in the scores on the BP, VT, SF, and RE subscales of the SF-36. Several previous studies have also shown that L-carnitine supplementation is commonly utilized in patients with inborn errors of carnitine metabolism and muscular carnitine deficiency [11], hemodialysis patients with muscular symptoms [3], and cirrhosis patients who experience muscle cramps [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-carnitine supplementation resulted in a decrease in the frequency of muscle cramps and in Wong-Baker FACES ® Pain Rating Scale score, and associated with an increase in the scores on the BP, VT, SF, and RE subscales of the SF-36. Several previous studies have also shown that L-carnitine supplementation is commonly utilized in patients with inborn errors of carnitine metabolism and muscular carnitine deficiency [11], hemodialysis patients with muscular symptoms [3], and cirrhosis patients who experience muscle cramps [14].…”
Section: Discussionmentioning
confidence: 99%
“…to Wong-Baker FACES ® Pain Rating Scale that ranged from 0 (no hurt) to 5 (hurts worst) [14]. The Wong-Baker FACES ® Pain Rating Scale was originally published in Whaley & Wong's Nursing Care of Infants and Children.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
“…(18) These questions ask patients to report on cramp frequency, location, duration, and severity separately for cramps during dialysis treatment and for cramps that occur at home following dialysis. (19,20,21) We further tested our instruments on a group of three dialysis patients who met all study eligibility criteria. The pretest subjects completed all study tasks as outlined below for the full trial, with the exception of receiving only one massage.…”
Section: Methodsmentioning
confidence: 99%
“…Other complications of diuretic therapy include hepatic encephalopathy, electrolyte disorders, gynaecomastia, and muscle cramps [13, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. If cramps are severe, diuretic dose should be decreased or stopped, and albumin infusion [37], baclofen, and l-carnitine may relieve symptoms [23][24][25][26][27]37].…”
Section: Diet and Diureticsmentioning
confidence: 99%